Amyloid β1-42 (Aβ1-42) Induces the CDK2-Mediated Phosphorylation of Tau through the Activation of the mTORC1 Signaling Pathway While Promoting Neuronal Cell Death - Lee, Ki Hoon; Lee, Sei-Jung; Lee, Hyun Jik; Choi, Gee Euhn; Jung, Young Hyun; Kim, Dah Ihm; Gabr, Amr Ahmed; Ryu, Jung Min; Han, Ho Jae (Frontiers in Molecular Neuroscience, 2017)
Alzheimer's disease (AD) is a neurodegenerative disorder, characterized by cognitive impairment and memory loss. Amyloid β 1-42 (Aβ) and hyper-phosphorylation of microtubule-associated protein tau have considered as major histological features in AD. However, the mechanism of how Aβ induces the hyper-phosphorylation of tau remains to clarify. In the present study, we investigated the underlying cellular mechanisms of Aβ with regard to the cell cycle regulatory protein-mediated phosphorylation of tau in promoting neuronal cell death. The oligomer Aβ (5 μM) significantly increased the level of caspase 3 cleavage and has ability to induce cytotoxicity in human neuroblastoma SK-N-MC cells. Aβ induced the degree of extracellular calcium influx via the L-type channel to facilitate the production of reactive oxygen species (ROS). Aβ signaling through ROS production is uniquely mediated by the activation of PI3K/Akt, which is in turn required for mTORC1 phosphorylation. mTORC1 activated by Aβ further increased the phosphorylation of eukaryotic translation initiation factor 4E (eIF4E), a binding protein (4E-BP1), and p70S6K1 to stimulate the HIF1α synthesis responsible for the induction of cyclinD1/CDK4 and cyclinE/CDK2, whereas it significantly attenuated the activation of autophagy. Aβ distinctively induced the CDK2-mediated phosphorylation of tau, which is responsible for microtubule destabilization in promoting neuronal apoptosis. In mouse hippocampal primary neurons, the apoptotic cell death induced by Aβ is highly susceptible to the mTORC1 signaling pathway. These results demonstrate that Aβ efficiently stimulates the mTORC1 signaling pathway to facilitate HIF1α synthesis and autophagy inhibition to promote the expression of cell cycle regulatory proteins, during which CDK2 uniquely stimulates tau phosphorylation for microtubule destabilization-mediated neuronal apoptosis.